Effects of Lactate on One Class of Group III (CT3) Muscle Afferents - Peterson, Rochelle A.; König, Christine; Zimmermann, Katharina; Barry, Christine M.; Wiklendt, Lukasz; Brookes, Simon J. H. (Frontiers in Cellular Neuroscience, 2020)
A class of Group III muscle afferent neurons has branching sensory terminals in the connective tissue between layers of mouse abdominal muscles (“CT3 muscle afferents”). These sensory endings are both mechanosensitive and metabosensitive. In the present study, responses of CT3 afferents to lactate ions and changes in temperature were recorded. Raising muscle temperature from 32.7°C to 37°C had no consistent effects on CT3 afferent basal firing rate or responses to either von Frey hair stimulation or to an applied load. Superfusion with lactate ions (15 mM, pH 7.4) was associated with an increase in firing from 6 ± 0.7 Hz to 11.7 ± 6.7 Hz (14 units, n = 13, P < 0.05, P = 0.0484) but with considerable variability in the nature and latency of response. Reducing the concentration of extracellular divalent cations, which mimicked the chelating effects of lactate, did not increase firing. Raised concentrations of divalent cations (to compensate for chelation) did not block excitatory effects of lactate on CT3 afferents, suggesting that effects via ASIC3 were not involved. Messenger RNA for the G-protein coupled receptor, hydroxyl carboxylic acid receptor 1 (HCAR1) was detected in dorsal root ganglia and HCAR1-like immunoreactivity was present in spinal afferent nerve cell bodies retrogradely labeled from mouse abdominal muscles. HCAR1-like immunoreactivity was also present in axons in mouse abdominal muscles. This raises the possibility that some effects of lactate on group III muscle afferents may be mediated by HCAR1.